2009
DOI: 10.1039/b909611f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of polar Diels–Alder reactions

Abstract: A good correlation between the activation energy and the polar character of Diels-Alder reactions measured as the charge transfer at the transition state structure has been found. This electronic parameter controls the reaction rate to an even greater extent than other recognized structural features. The proposed polar mechanism, which is characterized by the electrophilic/nucleophilic interactions at the transition state structure, can be easily predicted by analyzing the electrophilicity/nucleophilicity indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
490
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(518 citation statements)
references
References 56 publications
27
490
1
Order By: Relevance
“…In particular, the B3LYP/6-31G(d) calculations illustrate well the structure of transition states (TS) in cycloadditions between cyclopentadiene and CNA. This has been confirmed previously by the compilation of deuterium secondary kinetic isotope effects (SKIE) and results of quantum chemical calculations for polar Diels-Alder (P-DA [23] ) reaction between cyclopentadiene and (E)-2-phenylnitroethene [24]. The critical structures on the reaction paths were localized as in the case of the previously analysed reaction of (E)-2-phenyl-1-cyano-1-nitroethene with cyclopentadiene [22].…”
Section: Theoretical Exploration Of Reaction Pathssupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, the B3LYP/6-31G(d) calculations illustrate well the structure of transition states (TS) in cycloadditions between cyclopentadiene and CNA. This has been confirmed previously by the compilation of deuterium secondary kinetic isotope effects (SKIE) and results of quantum chemical calculations for polar Diels-Alder (P-DA [23] ) reaction between cyclopentadiene and (E)-2-phenylnitroethene [24]. The critical structures on the reaction paths were localized as in the case of the previously analysed reaction of (E)-2-phenyl-1-cyano-1-nitroethene with cyclopentadiene [22].…”
Section: Theoretical Exploration Of Reaction Pathssupporting
confidence: 63%
“…The large difference in the electrophilicity (Dx [ 2.7 eV) of the substrates indicates that reactions 1a-f ? 2 should be considered as P-DA reactions on the basis of Domingo terminology [23].…”
Section: Electronic Interactions Of Addentsmentioning
confidence: 99%
“…The presence of electron-withdrawing substituents in the dienophile, such as 1,1-dicyanoethylene (4, DCE), favors DA reactions by lowering the activation energy [9]. The corresponding acceleration is related with the polar character of the reaction, allowing for the classification of polar Diels-Alder (P-DA) reactions [7]. This substitution breaks the symmetry of the dienophile, making the C−C σ bond formation asynchronous [9].…”
Section: (Please Insert Figure 1)mentioning
confidence: 99%
“…Electron localization function [3][4][5][6] (ELF) analysis of bonding along the intrinsic reaction coordinate (IRC) of the DA reaction of cyclopentadiene (1, Cp) with ethylene (2), which is classified as a non-polar Diels-Alder (N-DA) reaction [7], indicates that this synchronous σ bond-formation process takes place according to the following pattern (see Figure 1) [8]: i) breaking of the three π bonds present in 1 and 2; ii) formation of two pseudodiradical species; iii) formation of the two new σ bonds by coupling of two pseudodiradical species, and iv) formation of the new C-C π bond present in cycloadduct (CA) 3 at the end of the reaction. It is interesting to remark that the transition state (TS) structure associated with this N-DA reaction is located at the end of phase i; consequently, the C-C bond formation has not started yet in the TS.…”
Section: (Please Insert Chart 1)mentioning
confidence: 99%
“…19 Notably, these reactions can be considered as polar1,3-dipolar cycloaddition (P-13DC). 20 Detailed analysis of the local electrophilicity indices on the reaction centers of nitroalkenes also revealed that the reaction was determined by the attack of nucleophilic atom of 1,3-dipole to β-position of nitroalkene, similarly as in the reactions of nitroethene with nitrones. 21 …”
Section: Resultsmentioning
confidence: 99%